2003
DOI: 10.1097/00061198-200306000-00009
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Monitoring of Intraocular Pressure in Glaucoma Management: A Retrospective Review

Abstract: Twenty-four-hour monitoring of IOP frequently led to a change of glaucoma management by identifying IOP fluctuations and spikes. High IOP and wide diurnal IOP variation are considered major risk factors for glaucoma progression, and standard clinic follow-up evaluations failed to identify these phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
133
0
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(153 citation statements)
references
References 19 publications
5
133
0
15
Order By: Relevance
“…In our study, the mean pressure-lowering effect of bimatoprost (7.9 mmHg, 33.4%) and latanoprost (7.1 mmHg, 30.6%) are less than that reported in the study by Walters et al 21 Lack of variation has been shown in several studies to be important in helping to prevent long-term progressive VF loss with glaucoma. 1,2,22 We additionally evaluated the mean range of IOP as Konstas et al's 14 study. The untreated mean range of IOP is approximately 7 mmHg in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mean pressure-lowering effect of bimatoprost (7.9 mmHg, 33.4%) and latanoprost (7.1 mmHg, 30.6%) are less than that reported in the study by Walters et al 21 Lack of variation has been shown in several studies to be important in helping to prevent long-term progressive VF loss with glaucoma. 1,2,22 We additionally evaluated the mean range of IOP as Konstas et al's 14 study. The untreated mean range of IOP is approximately 7 mmHg in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective chart review of 29 treated POAG and NTG patients, Hughes et al 39 found that although the mean office IOP determined in previous visits was similar to the mean 24-hour values, the peak IOP during 24-hour monitoring was almost 5 mm Hg higher than the peak office IOP. The mean circadian IOP variation amplitude was 9.4 mm Hg.…”
Section: Circadian Iop Variations In Treated Eyesmentioning
confidence: 92%
“…Studies in humans describe the use of serial measurements of intraocular pressure (IOP) during periods of 24hours for the management of patients with glaucoma (Hughes et al 2003, Barkana et al 2006, Bagga et al 2009). The preliminary results of the development of an IOPC protocol for serial use in dogs with elevated IOPs found that IOPCs might be useful for monitoring IOP in this species, but warned of the development of superficial corneal ulceration, which was theorized to pose a likely challenge (Viera da Silva and Sanchez 2010).…”
Section: Introductionmentioning
confidence: 99%